Address campus violence through training for students, advocating with legislators. Issue 9 (16th December 2015) - Miles, David
Abstract : In late August or early September, college and universities opened their doors for the start of another semester. Bright‐eyed freshmen arrived at the campus wondering what college life is all about, while upperclassmen returned for another semester, counting down the months and days to their graduation. For many, the start of college represents a newfound freedom as well as facing the challenges associated with this new journey. For all college students, this should be an exciting time of their life.